Forecasting Crop Production Based On Soil Data and Detection of Diseases Using Machine Learning - Riyaz, M. Mohammed; Gopalakrishnan, V.; Kalidasan, S. (Journal of Soft Computing Paradigm, 2022)
Estimating crop creation has been a consistent worry since the start of the historical backdrop of agribusiness. Guaging strategies have advanced, as has horticulture itself and the determinations of the gauges required. The individuals who utilize figure information are continuously looking for more noteworthy precision, granularity, likeness, and idealness. The people who produce the information or add to their creation generally work under monetary and specialized requirements. Acquiring opportune information presents an undeniable test. Today, the human, institutional, specialized, and monetary foundation behind crop figures and proposal gauges specifically can be unquestionably complicated. This distribution gives experiences into such complex information frameworks at the nation level. It features great practices and prospects for what's to come. The distinguishing proof and location of sicknesses of plants is one of the central matters which decide the deficiency of the suggestion of yield creation and agribusiness. The investigations of plant illness are the examination of any noticeable places in any part of the plant, such as any spots or conceals, which assists in distinguishing between two plants. The manageability of the plant is one of the central issues for rural turn of events. The discovery of plant sicknesses is undeniably challenging to get right. The recognizable proof of the illness requires loads of work and ability, bunches of information in the field of plants and the investigations of the identification of those sicknesses. Thus, picture handling is utilized for the identification of plant infections. The detection of infections follows the strategies for picture procurement, picture extraction, picture division, and picture pre-handling.
Keywords: Machine Learning; crop production; image pre-processing; crop recommendation prediction